2008
DOI: 10.1039/b716306a
|View full text |Cite
|
Sign up to set email alerts
|

A highly active and reusable copper(i)-tren catalyst for the “click” 1,3-dipolar cycloaddition of azides and alkynes

Abstract: The copper(I) complex [Cu(C18(6)tren)]Br 1 (C18(6)tren = tris(2-dioctadecylaminoethyl)amine) which exhibits a good stability towards aerobic conditions is a versatile, highly reactive and recyclable catalyst for the Huisgen cycloaddition of azides with terminal or internal alkynes and is a useful catalyst for the preparation of "click" dendrimers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
132
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(136 citation statements)
references
References 33 publications
4
132
0
Order By: Relevance
“…This procedure appears to be regioselective and gives only the N-1 isomer for pyrimidines and N-9 isomer for adenine ( Table 1). The structures of the nucleosides 2a-h were determined from their spectral (NMR 1 H, 13 C, and Mass) data and found to be in agreement with the literature 8d . In preliminary experiments, azido-2,3,5-tri-O-benzoylribose 16 (azidosugar) 3 was chosen for the template reaction with propargyl-uracil 2a.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…This procedure appears to be regioselective and gives only the N-1 isomer for pyrimidines and N-9 isomer for adenine ( Table 1). The structures of the nucleosides 2a-h were determined from their spectral (NMR 1 H, 13 C, and Mass) data and found to be in agreement with the literature 8d . In preliminary experiments, azido-2,3,5-tri-O-benzoylribose 16 (azidosugar) 3 was chosen for the template reaction with propargyl-uracil 2a.…”
Section: Resultsmentioning
confidence: 59%
“…Deblocking of the benzoyl protecting groups was performed using methanolic ammonia (saturated at 0°C) at room temperature and gave 1,2,3-triazole ribonucleosides 9a-h in a 40-55% yield. The structures of the nucleosides were determined from their spectral ( 1 H, 13 C NMR and Mass) data. The mechanism for this Na2CuP2O7 -catalyzed synthesis of 1,2,3-triazole ribonucleosides need much more studies, but we offer the following tentative hypothesis.…”
Section: Methodsmentioning
confidence: 99%
“…In the past few years, several other polydentate aza-ligand frameworks have also been found to aid CuAAC reactions. [14][15][16][17][18][19] We recently found that TBTA also accelerates CuA C H T U N G T R E N N U N G (OAc) 2 -mediated AAC reactions that involve nonchelating azides. [9] In a number of reactions that proceed sluggishly under Cu-A C H T U N G T R E N N U N G (OAc) 2 -mediated conditions, yields of over 90 % were achieved in the presence of TBTA within 1 or 2 h. In this work, we investigated the acceleratory effects of other polytriazoles in CuA C H T U N G T R E N N U N G (OAc) 2 -mediated AAC reactions.…”
Section: Introductionmentioning
confidence: 99%
“…16 However, it displayed a gradual decrease in activity when reused either because of oxidation of the copper(I) centers or metal leaching. Better results were obtained with related complex 5, 17 bearing a crowded tripodal ligand to effectively protect the copper center against oxidation while keeping it highly active.…”
Section: Amine Ligandsmentioning
confidence: 96%
“…6 Nevertheless, catalysts 30 and 5 can mediate the reaction of benzyl azides and 3-hexyne (Scheme 13). 52,17 Even though these reactions are not ideal (and only one alkyne was studied), they proved that alternative activation pathways are possible for copper-catalyzed cycloadditions. It is important to note that in the presence of CuBr under similar conditions, only sluggish reactions were observed, which proves the crucial role of the ligands in this reaction.…”
Section: Reactions Of Organic Azides and Internal Alkynesmentioning
confidence: 99%